Leadership of the principal in improving the professional competence of teachers in the digital age - Novi Andri Yani; Muhammad Kristiawan; Alfroki Martha (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The achievement of the vision, mission and objectives of education depends on the wisdom and leadership skills of the principal as the leader of the education unit. While in general, this research aims to (1) Describe the leadership of the principal in improving the professional competence of teachers in the digital age. (2) Know the supporting and inhibiting factors of the principal in improving the professional competence of teachers in the digital age. The result of this research was obtained that the implementation of the type of leadership of the principal at SMA Negeri 4 OKU by the principal received a good response from subordinates, it’s namely democratically, he always gave a good example to the teacher, so there is an improvement in the competence of the teacher's personality, delegate the teachers incidental related to the duties of officially and provide motivation to students, and open attitude becomes a place of consultation and implementation through decision making related to increasing the professionalism of teachers through meetings or deliberations, show how the way teachers are happy to carry out the verdict and feel satisfaction. The supporting factor of the principal’s leadership type in improving the professional competence of teachers at SMA Negeri 4 OKU is adequate from infrastructure facilities, thus supporting the teaching, training or learning process in schools. Furthermore, the obstacles encountered include, the limitations of teacher training programs outside office hours, there are still some teachers who are not active, and the results of the training can not affect their friends, then in the rules that have been determined there are still teachers who are less disciplined.